CHARACTERISTICS OF SELECTED HEMATOLOGICAL INDICES IN PATIENTS WITH POLYCYTHEMIA VERA AT NATIONAL INSTITUTE OF HEMATOLOGY AND BLOOD TRANSFUSION DURING 2021-2023 (Vietnam Journal of Community Medicine, 2026)
Objectives: Describe some peripheral blood cell indicators of polycythemia vera patients at the National Institute of Hematology and Blood Transfusion in the period 2021-2023; describe the characteristics of bone marrow index in patients with polycythemia vera at National Institute of Hematology and Blood Transfusion in the period 2021-2023.Subjects and methods: Cross-sectional descriptive study, retrospective medical records of 72 patients with a confirmed diagnosis of polycythemia vera at the National Institute of Hematology and Blood Transfusion from 1/2021 to 12/2023.Results: This disease occurs in both sexes with a male/female ratio of 2.33/1, the average age is 62 years old. Patients with positive JAK2 V617F gene account for 90.3%, patients with negative JAK2 V617F gene account for 9.7%. In peripheral blood, RBC, hemoglobin, and hematocrit increased by 6.94 T/l, 196 g/l, and 0.605 l/l, respectively; normal MCV, MCH, and MCHC indexes are 89.4 fl, 28.7 pg, 323 g/l respectively;the white blood cell count was elevated, with a median level of 13.46 G/l; while platelet count is within the normal range (median 433 G/l). On the bone marrow, there is bone marrow cell count increased by 104.4 G/l. Bone marrow biopsy shows mainly increased red blood cell proliferation (90.3%), white blood cell proliferation (65.3%), platelet proliferation (54.2%), and platelet morphology with morphological disorders (65.3%).Conclusion: There are changes in the characteristics of some peripheral blood and bone marrow indices in patients with polycythemia vera, including myelograms and bone marrow biopsies.
Keywords: Polycythemia vera, peripheral blood cells, bone marrow.